Geological archive of the onset of plate tectonics - Cawood, P.; Hawkesworth, C.; Pisarevskiy, Sergei; Dhuime, B.; Capitanio, F.; Nebel, O. (The Royal Society Publishing, 2018)
© 2018 The Author(s) Published by the Royal Society. All rights reserved. Plate tectonics, involving a globally linked system of lateral motion of rigid surface plates, is a characteristic feature of our planet, but estimates of how long it has been the modus operandi of lithospheric formation and interactions range from the Hadean to the Neoproterozoic. In this paper, we review sedimentary, igneous and metamorphic proxies along with palaeomagnetic data to infer both the development of rigid lithospheric plates and their independent relative motion, and conclude that significant changes in Earth behaviour occurred in the mid- to late Archaean, between 3.2 Ga and 2.5 Ga. These data include: sedimentary rock associations inferred to have accumulated in passive continental margin settings, marking the onset of seafloor spreading; the oldest foreland basin deposits associated with lithospheric convergence; a change from thin, new continental crust of mafic composition to thicker crust of intermediate composition, increased crustal reworking and the emplacement of potassic and peraluminous granites, indicating stabilization of the lithosphere; replacement of dome and keel structures in granite-greenstone terranes, which relate to vertical tectonics, by linear thrust imbricated belts; the commencement of temporally paired systems of intermediate and high dT/dP gradients, with the former interpreted to represent subduction to collisional settings and the latter representing possible hinterland back-arc settings or ocean plateau environments. Palaeomagnetic data from the Kaapvaal and Pilbara cratons for the interval 2780-2710Ma and from the Superior, Kaapvaal and Kola-Karelia cratons for 2700-2440Ma suggest significant relative movements. We consider these changes in the behaviour and character of the lithosphere to be consistent with a gestational transition from a non-plate tectonic mode, arguably with localized subduction, to the onset of sustained plate tectonics.